WANITA PEKERJA KERAS DALAM KARYA REALIS KONTEMPORER - Seftian Hidayat, Ir. Drs. Heldi, M.Si., Ph.D., Drs. Ariusmedi, M.Sn. (Universitas Negeri Padang, 2018)
The purpose of visualizing the work of contemporary realist painting in the background of the issue of the situation and social conditions of society, especially hard-working women. Women play a role as housewives to take care of the family, choosing to work hard in meeting the needs of the economy. Methods and process of painting through several stages of preparation stage, elaboration stage, synthesis stage, concept relasation phase and completion stage. The works that are visualized are: Fighting Tiredness, For the Ideal, Filling One By One, Hope Behind Smile, Being Backbone, Endless Struggle, Scraping One by One, Against Pain, High Angle, BeautifulHope.Keywords: Women, Workers, Hard, Realists, Contemporary.